2019
DOI: 10.1002/lno.11127
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of primary production during drought in a temperate watershed is greater in larger rivers than headwater streams

Abstract: Drought is common in rivers, yet how this disturbance regulates metabolic activity across network scales is largely unknown. Drought often lowers gross primary production (GPP) and ecosystem respiration (ER) in small headwaters but by contrast can enhance GPP and cause algal blooms in downstream estuaries. We estimated ecosystem metabolism across a nested network of 13 reaches from headwaters to the main stem of the Connecticut River from 2015 through 2017, which encompassed a pronounced drought. During drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 85 publications
3
40
1
Order By: Relevance
“…Specifically, drought caused a significant reduction in aerobic respiration along the experimental stream reach, which decreased from −403 ± 172 to −130 ± 81 mmol O 2 m −2 d −1 . Previous studies testing the effects of drought, either experimentally or under natural conditions, have shown that low flows can either enhance 31,32 or reduce 33 rates of stream aerobic respiration. In our case, aerobic respiration decreased nonlinearly with WRT (r 2 = 0.41; p < 0.001; n = 111), ostensibly because the biochemical O 2 demand driven by aerobic respiration greatly exceeded the resupply of O 2 to hyporheic sediments as drought ensued.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, drought caused a significant reduction in aerobic respiration along the experimental stream reach, which decreased from −403 ± 172 to −130 ± 81 mmol O 2 m −2 d −1 . Previous studies testing the effects of drought, either experimentally or under natural conditions, have shown that low flows can either enhance 31,32 or reduce 33 rates of stream aerobic respiration. In our case, aerobic respiration decreased nonlinearly with WRT (r 2 = 0.41; p < 0.001; n = 111), ostensibly because the biochemical O 2 demand driven by aerobic respiration greatly exceeded the resupply of O 2 to hyporheic sediments as drought ensued.…”
Section: Resultsmentioning
confidence: 99%
“…To normalize and compare Q from the studied streams with different catchment areas, we report specific discharge (mm day −1 ). To isolate drought hydrological conditions from the rest of the periods, we delineated the specific discharge and grouped studied responses based on percentile distributions of the historical (1980-2018) discharge records in the catchment 32 : drought (0th-10th percentile; n = 59), low flow (10th-20th percentile; n = 22), baseflow (20th-50th percentile; n = 90), and high flow (50th-100th percentile; n = 193).…”
Section: Methodsmentioning
confidence: 99%
“…Using continuous measures of environmental conditions such as flow and integrating those measures with high‐resolution time series of ecosystem metabolism, we have the opportunity to determine when and where the impacts of physical constraints and disturbance on energy resources may constrain community membership or reduce the total consumer production and biomass. For example, studies using high‐frequency measurements of ecosystem metabolism and GPP have already revealed that in many systems low flows coincide with periods of high light availability (Hensley et al 2019; Hosen et al 2019) resulting in higher rates of photosynthetic autochthonous production (Hall et al 2015; Hosen et al 2020). These integrated studies suggest that autochthonous production may counterbalance allochthonous production in temperate stream networks with potential implications for consumer production and biomass.…”
Section: Figmentioning
confidence: 99%
“…Hydrology influences autochthonous production via channel depth and water clarity. Riverine water clarity increases during low flow/long travel time conditions due to lower levels of highly chromophoric allochthonous organic matter (Hensley et al, 2019) and particulates (Hosen et al, 2019). Increased light availability during low flow conditions favours increased aquatic photosynthesis (Hall et al, 2015; Hosen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Riverine water clarity increases during low flow/long travel time conditions due to lower levels of highly chromophoric allochthonous organic matter (Hensley et al, 2019) and particulates (Hosen et al, 2019). Increased light availability during low flow conditions favours increased aquatic photosynthesis (Hall et al, 2015; Hosen et al, 2019). Greater travel time during low flows allows more time for photosynthetic communities to develop biomass (Glibert et al, 2014; Paerl et al, 1998; Vannote et al, 1980).…”
Section: Introductionmentioning
confidence: 99%